Ambivalensi Agama dan Gerakan Sosial Kristen - Yohanes Hasiholan Tampubolon; Yusuf Wibisono; Asep Muhyidin (Te Deum (Jurnal Teologi dan Pengembangan Pelayanan), 2026)
This article examines the ambivalence of religion in Christian social movements through an analysis of previous studies conducted in Latin America, South Africa, the Philippines, and other contexts. The analysis demonstrates how Christian symbols and religious practices simultaneously function as forces of emancipatory liberation and as mechanisms for legitimizing the status quo. The study employs a critical interpretive review of the literature on Christian-based social movements across diverse historical and geographical settings. The findings identify three principal mechanisms underlying the ambivalence of Christianity: internal struggles over religious meaning, historical transformations driven by political and economic crises, and the influence of actors' positions within social hierarchies in shaping progressive or conservative orientations. Periods of crisis tend to strengthen Christianity's emancipatory potential through grassroots communities, whereas alignment with dominant social classes encourages accommodation to existing political and social structures.